Pain treatment today - Current standing of pain treatment in Germany - Ostgathe, Christoph; et al. (AINS - Anästhesiologie. Intensivmedizin. Notfallmedizin. Schmerztherapie., 2003)
Beyond doubt the provision of pain therapy for patients with acute and chronic pain in Germany has improved over the last 30 years. This positive development comprises i.e. the growing impact of acute pain services on the treatment of patients with postoperative pain and the implementation of new developments in research into the clinical setting of obstetric pain therapy. Nevertheless, the provision of pain therapy for patients with chronic pain syndromes, for children, and in the fields of cancer pain and palliative medicine is neither qualitatively nor quantitatively sufficient.
Keywords: Education; Germany; Pain; Pain therapy; Research